Dravyaguna Principles As Predictive Tools In Ayurvedic Pharmacology: A Review - Kushwaha, Ranjeet Kumar; Tiwari, Sampurna Nand; Rajak, Alok Ranjan; Ranjan, Raman (Journal of Neonatal Surgery, 2025)
Ayurveda, the ancient Indian system of medicine, offers a comprehensive pharmacological framework grounded in natural principles that emphasize the interplay between the properties of substances and their effects on the human body. The branch of Dravyaguna Vijnana (Ayurvedic pharmacology) encompasses the detailed study of Rasa (taste), Guna (qualities), Veerya (potency), Vipaka (post-digestive transformation), and Prabhava (specific action). These principles not only classify substances but also serve as predictive tools for assessing their therapeutic potential, even in the absence of experimental validation. Unlike modern pharmacology, which often focuses on isolated chemical constituents and receptor-specific actions, the Ayurvedic model is holistic, integrative, and tailored to individual constitution (Prakriti). This review critically explores each of the Panchavidha Gunas—highlighting their theoretical foundations, clinical significance, and potential correlations with modern pharmacodynamic and pharmacokinetic concepts. It further discusses how these principles can guide empirical drug formulation and contribute to the growing field of personalized and integrative medicine. Contemporary research supports the potential of Dravyaguna parameters in identifying bioactivity, forecasting therapeutic outcomes, and understanding herb–drug interactions. Moreover, advancements in pharmacogenomics and systems biology provide a promising platform to scientifically validate these ancient concepts.By integrating traditional Ayurvedic wisdom with modern scientific methodologies, Dravyaguna principles can play a pivotal role in bridging ethnopharmacology and modern drug discovery. The review underscores the relevance of these timeless concepts in developing safer, more effective, and personalized therapeutic interventions in today’s evolving medical landscape